2020
DOI: 10.1101/2020.06.11.145573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective ERK/Akt activity waves orchestrate epithelial homeostasis by driving apoptosis-induced survival

Abstract: Cell death events continuously challenge epithelial barrier function, yet are crucial to eliminate old or critically damaged cells. How such apoptotic events are spatio-temporally organized to maintain epithelial homeostasis remains unclear. We observe waves of Extracellular Signal-Regulated Kinase (ERK) and AKT serine/threonine kinase (Akt) activity pulses that originate from apoptotic cells and propagate radially to healthy surrounding cells. Such a propagation requires Epidermal Growth Factor Receptor (EGFR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 65 publications
7
31
0
Order By: Relevance
“…Outer cells displayed ERK frequencies of typically one pulse every 2 hours on average, while inner cells pulsed rarer and often did not exhibit ERK pulses at all ( Figure 4A). This is consistent with a similar phenomenon in serumstarved 2D MCF10A cultures in which dying cells evoke local waves of single-cell ERK pulses that each induce survival for approximately 4 hours (Gagliardi et al, 2020).…”
Section: Stage 2 Acini Display Erk Waves That Specify Different Erk Fsupporting
confidence: 88%
See 2 more Smart Citations
“…Outer cells displayed ERK frequencies of typically one pulse every 2 hours on average, while inner cells pulsed rarer and often did not exhibit ERK pulses at all ( Figure 4A). This is consistent with a similar phenomenon in serumstarved 2D MCF10A cultures in which dying cells evoke local waves of single-cell ERK pulses that each induce survival for approximately 4 hours (Gagliardi et al, 2020).…”
Section: Stage 2 Acini Display Erk Waves That Specify Different Erk Fsupporting
confidence: 88%
“…We then imaged single-cell ERK dynamics in stage 1 acini using 3D confocal spinning disk microscopy of both the H2B and ERK KTR channels with time resolutions of 3 -5 minutes, until acini started to suffer from phototoxicity (which was observed after 10 -23 hours of imaging). Visual inspection of micrographs of stage 1 acini revealed that different cells displayed asynchronous ERK pulses ( Figure 2A) as previously observed in 2D cultures (Aikin et al, 2020;Albeck et al, 2013;Gagliardi et al, 2020). To quantify single-cell ERK activity trajectories, we used a custom-modified version of the opensource LEVER software (Wait et al, 2014;Winter et al, 2016) to segment and track nuclei based on their H2B signal; and to extract ERK activity trajectories by calculating the ratio of the ERK KTR intensities in the nucleus over a voxel mask around the nucleus ( Figure 2B).…”
Section: Stage 1 Proliferative Acini Exhibit Spontaneous Egfr-dependesupporting
confidence: 80%
See 1 more Smart Citation
“…H2B-miRFP703, ERK-KTR-mTurquoise2 and FoxO3a-mNeonGreen constructs were generated and subcloned in the piggy PiggyBac vectors pMP-PB, pSB-HPB and pPB3.0.Blast as previously described 17 . Upon transfection of these plasmids with FuGene (Promega), cells were treated with 2.5 μg/ml Puromycin, 25 μg/ml Hygromycin and 5 μg/ml Blasticidin to select stably expressing cells.…”
Section: Cell Culture and Biosensor Imagingmentioning
confidence: 99%
“…To obtain single-cell bivariate signalling trajectories of ERK and Akt activities we used a dedicated image analysis pipeline, as previously described 17 . First, we trained a random forest classifier based on different pixel features (Ilastik 18 ) to separate H2B-miRFP703 fluorescence from background signal.…”
Section: Automated Image Analysismentioning
confidence: 99%